2019
DOI: 10.3389/fbioe.2019.00331
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Channel Selection for Gesture Classification for Prosthesis Control Using Force Myography: A Case Study

Abstract: Background: Various human machine interfaces (HMIs) are used to control prostheses, such as robotic hands. One of the promising HMIs is Force Myography (FMG). Previous research has shown the potential for the use of high density FMG (HD-FMG) that can lead to higher accuracy of prosthesis control. Motivation: The more sensors used in an FMG controlled system, the more complicated and costlier the system becomes. This study proposes a design method that can produce powered prostheses with performance comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Signals used in this method can be potentially acquired throughout extended periods of time. FSR signals are easy to process, making this method computationally efficient [28,29]. Another advantage of this method is that it does not require direct contact with the skin and is less prone to errors due to environmental changes compared to some of the alternative methods.…”
Section: Discussionmentioning
confidence: 99%
“…Signals used in this method can be potentially acquired throughout extended periods of time. FSR signals are easy to process, making this method computationally efficient [28,29]. Another advantage of this method is that it does not require direct contact with the skin and is less prone to errors due to environmental changes compared to some of the alternative methods.…”
Section: Discussionmentioning
confidence: 99%
“…Again, Sakr et al showed the possibility of predicting force in dynamic conditions by using FSRs worn around the arm [150]. Ahmadizadeh et al explored the application of feature selection to three high-density FMG datasets in order to reduce its dimensionality and, at the same time, achieve the same performance but with lower cost and complexity [151]. Xiao et al proposed a novel FMG system, consisting of a strap embedded with eight FSRs, to detect different forearm positions for controlling a custom-made forearm pronation/supination exoskeleton [152].…”
Section: Muscle Gross Motion-based Hmismentioning
confidence: 99%
“…Over the last few years, multiple non-invasive control methods of prosthetic hands have been introduced and investigated; for example, surface electromyography (sEMG) (Fougner et al, 2012 ; Farina et al, 2014 ; Krasoulis et al, 2017 ; Pizzolato et al, 2017 ; Ameri et al, 2018 ; Li et al, 2018 ; Leone et al, 2019 ; Olsson et al, 2019 ; Junior et al, 2020 ), electroneurography (ENG) (Cloutier and Yang, 2013 ; Paul et al, 2018 ), mechanomyography (MMG) (Xiloyannis et al, 2015 ; Wilson and Vaidyanathan, 2017 ), and force myography (FMG) (Rasouli et al, 2015 ; Sadeghi and Menon, 2018 ; Ahmadizadeh et al, 2019 ). In particular, sEMG is a non-invasive technique for measuring the electrical activity of groups of muscles on the skin surface, which makes it a simple and straightforward way to allow the user to actively control the prosthesis.…”
Section: Introductionmentioning
confidence: 99%